Discussion of Students' E-book Reading Intention With the Integration of Theory of Planned Behavior and Technology Acceptance Model - Luo, Yu-Zhou; Xiao, Yue-Ming; Ma, Yu-Yang; Li, Chao (Frontiers in Psychology, 2021)
The emergence of e-books with the characteristics of easy access and reading any time anywhere is a subject of debate in academia. Topics include the use of e-books in libraries, their use in support teaching, new possibilities for reading activities, potential uses for library archives, and the motivation and intention of e-book users. Students at Guilin University of Technology participated in a survey. Of the 300 copies of the questionnaire distributed, 263 valid copies were returned, a retrieval rate of 88%. The research results show that (1) Usability and reading need are the key factors in e-book usage. Usability refers to convenient keyword searches, portability, and any time reading. E-books are considered to make searching and reading large amounts of data easier. (2) E-books are not restricted to time and space so that the overall reading quantity is increasing. Readers become accustomed to reading e-books, and the quality of their digital reading is gradually enhanced. (3) Students should complete e-book use courses offered by libraries to enhance their familiarity with e-books and their use of e-book software, thereby enhancing postgraduate student readers’ e-book information literacy. The results of the research prompt suggestions to enhance the promotion of reading and e-book information to encourage student readers’ e-book reading intention.